Accommodation eWOM in the sharing economy: automated text comparisons from a large sample. Issue 2 (17th February 2021) - Pitt, Christine; Plangger, Kirk; Eriksson, Theresa
ABSTRACT: Across many industries, individuals are increasingly relying on customer ratings and reviews on social media. While customer reviews often provide detailed diagnostic information about experiences, customer ratings often reduce the experience down to a simple number. Moreover, there is evidence to support that customer rating inflation is occurring on social media sites over time, especially in the sharing economy, and especially with regard to travel and tourism experiences. This paper conceptualizes how customer experiences are reduced into customer reviews and further abridged into customer ratings in both the traditional and sharing economy contexts. We propose that customers observe how service providers present themselves as a professional (established chain hotel) or amateur (owner operated vacation rental apartment), and then form different service expectations and perceptions accordingly. We investigate 55, 110 customer reviews and ratings of New York City's accommodation providers and indeed find evidence of rating inflation over the eight years studied.